2006
DOI: 10.4049/jimmunol.177.8.4962
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Hypoxia-Inducible Factor 1α and Its Activation-Inducible Short Isoform I.1 Negatively Regulate Functions of CD4+ and CD8+ T Lymphocytes

Abstract: To evaluate the role of hypoxia-inducible factor 1α (HIF-1α) and its TCR activation-inducible short isoform I.1 in T cell functions, we genetically engineered unique mice with: 1) knockout of I.1 isoform of HIF-1α; 2) T cell-targeted HIF-1α knockdown; and 3) chimeric mice with HIF-1α gene deletion in T and B lymphocytes. In all three types of mice, the HIF-1α-deficient T lymphocytes, which were TCR-activated in vitro, produced more proinflammatory cytokines compared with HIF-1α-expressing control T cells. Surp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
172
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(186 citation statements)
references
References 32 publications
12
172
0
2
Order By: Relevance
“…Recent literature suggests that blunted HIF-1a expression results in a net proinflammatory program evident by increased production inflammatory cytokines upon TCR engagement [6]. Similar results were obtained upon knocking out HIF-1 selectively in T cells [7]. Additionally, HIF-1a was reported to play an inhibitory role in the regulation of T-cell receptor signal transduction by controlling intracellular calcium balance [8].…”
mentioning
confidence: 62%
“…Recent literature suggests that blunted HIF-1a expression results in a net proinflammatory program evident by increased production inflammatory cytokines upon TCR engagement [6]. Similar results were obtained upon knocking out HIF-1 selectively in T cells [7]. Additionally, HIF-1a was reported to play an inhibitory role in the regulation of T-cell receptor signal transduction by controlling intracellular calcium balance [8].…”
mentioning
confidence: 62%
“…The first indications that HIF1␣ had both immunosuppressive and tissue-protective roles were provided by in vivo studies showing dramatically increased autoimmunity and tissue damage in chimeric mice that possessed genetic deficiency of HIF1␣ in their T-and B-cells (17). Direct evidence that both isoforms of HIF1␣ are immunosuppressive in activated T-cells was provided by studying T-cells from mice with complete genetic knockout of HIF1␣ isoforms (18). Sitkovsky and colleagues (18) have shown that the HIF1␣I.1 isoform is anti-inflammatory in T-cells, thereby preventing T-cell activation in vivo.…”
mentioning
confidence: 99%
“…It has been shown that HIF-1a plays crucial roles in T cell survival and functions. 11,12 However, the role of HIF-2a in T/NKT cells has not been explored.…”
mentioning
confidence: 99%